Peningkatan Kualitas Nutrisi Limbah Kulit Buah Kakao dan Daun Lamtoro Melalui Fermentasi Sebagai Basis Protein Pakan Ikan Nila - Nur Indariyanti; Rakhmawati Rakhmawati (Jurnal Penelitian Pertanian Terapan, 2013)
This experiment purposed to increase quality of cacao leader by product (CLBP) and leucaena leucocephala leader (LLL) that fermentated in niloticus feed. The variables observed was decrease of limiting factor there was crude fiber, selulose,hemiselulose, lignin, Neutral detergent fiber (NDF) fraction, Acid detergent fiber (ADF) fraction, theobromin anti nutrient on CLBP, mimosin on LLL an digestibility trials . digestibility trials done to niloticus with average weight of 35-40 gr and density of 10 fish/aquarium (80x40x40 cm). The result of experiment showed that CLBP fermentation with Aspergillus niger can decrease crude fiber 51,48%, and increased protein contain 78,67, while decreation of crude fiber on LLL 46,61% and protein increased 18,25%, total amino acid of CLBP increased 19,35% and on LLL 7,94. %. Result of digestibility of niloticus increased total indigestion of CLBP 52,37% to 60,3%, and 54,89% to 61,43% on LLL. While biology examination was done on Niloticus which 35-40 gram/fish. The best result of growth performance and feed conversion ratio due to this group of fish on feed composition 12% CLBP fermentation, 8% LLL fermentation and 6% CLBP fermentation, 24% LLL fermentation. Palability and survival rate due to this group showed not significant different (P<0,05). Keywords: cacao leader by product,leucaena leucocephala leader, fermentation , niloticus